(3gOGjI GdYGed aj GdYed HGdQHY GdcGeds
(3ChdgG (B:s
(3GdMeO ddg GdPj QSe aj UaMGJ eUfhYGJg bhGWY GdOdGFd CeG HYO agPg QSGdI dNUJ ajgG eMGSf GdQSGFd hNUUJgG HGge eG jJYdb GdQHY GdcGed s
(3BNQgG (B:s
(3Cf JfRd ef GdSJjf aj GdLjhH GdeShWI HeG JQjO aj YOO CLRGFI hJfRd ef LjH GdJeGe dLjhH s
(3Vef eLehY , JQJjHgG (B: 9s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3eJaQbGJs